The Influence of Instructor Learning Approaches and Personality on the Learning Outcomes of Clothing Production Assistant Trainees (Sewing) for the Year 2022-2023 - Winda Safitri; Lili Dasa Putri (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2026)
This research was driven by poor result of study obtained by Seamstress of Training program at BLK Lubuk Sikaping, in 2022-2023. This matter perceived from marks obtained by Trainee, post traineeship, there were many trainee were obtained mark under KKM ( Minimum Completeness Criteria ), which was scored still under 80. The purpose of this research, 1)To view, If the instructor teaching approaches could affect the results of study of Seamstress trainee at BLK Lubuk Sikaping, 2)To oversee If the Trainee personality/ Behaviour could influenced their marks as a result of study of seamstress at BLK Lubuk Sikaping. 3)To overlook If Instructor teaching approach and trainee personality could influenced towards their marks ( study results ), of seamstress trainee at BLK Lubuk Sikaping.Research approach use in this study is quantitative descriptive, data collected from all participants of seamstress traineeship total of 128 people in 2022-2023.Data collection methods use in this study was cluster random sampling in which was done by sampling collected randomly towards 79 individuals or 62% out of 128 participants. Data collection methods used by researcher in this research was Questionnaires, which used to gather information from participants. Therefore, Data analysis techniques used was Multiple Linear Regression. Results of the research shown that : 1)Seamstress Traineeship program’s instructor teaching approach was poor, this matter can beviewed where respondents of research tend to choose alternative answer as “ SELDOM”, 2)Seamstress Traineeship program’s personalities were categorised as “ Fairly Good”, this can be viewed where respondents of research had chosen alternative answer as “ OFTEN “, 3) Study results of Seamstress traineeship program categories as low/poor as out of 128 trainee,at approximately 68% had obtained marks under the minimum completeness criteria ( KKM), 4) There were significant influences between Trainer teaching approach and the results of study, 5) There were not significant influences between Trainee personalities and their results of study 6) Mutually, there were not any influences between trainer teaching approach and trainee personality towards their marks of Alumni seamstress Traineeship program at BLK Lubuk Sikaping in 2022-2023.